Comparative Effect of Hybrid and Thermally Upgraded Kraft Insulating Papers on Degradation of Mineral and Natural Ester Insulating Oils by Accelerated Ageing Tests - Wilhelm, Helena M.; Fernandes, Paulo; Fernandes, Kethlyn Moscon Paulo; Fornari, Mayara; Peres, Sergio; Bender, Vitor; Marchesan, Tiago; Marek, Richard; Moraes, Germano; Veloso, Nelson; Martins, Luan; Marin, Marco (Electrical Insulation Conference and Electrical Manufacturing Expo, 2023)
The performance of a new insulating oil/paper system can be evaluated by accelerated ageing tests. In this work, the degree of polymerization (DP) and the tensile strength of two insulating papers are determined: hybrid paper (HP) and thermally upgraded kraft paper (TUK). A natural ester insulating oil (NEIO), a soybean based-product was selected. Insulating papers and pressboards were dried until reaching a moisture content between 0.25 and 0.5% and, afterwards, they were vacuum impregnated with both insulating oils, NEIO and mineral insulating oil (MIO). The list of materials described in IEEE Std C57.100 defined for distribution transformer transformers was used. In our study, 4 accelerated ageing temperatures are planned for testing: 165, 175, 185 and 195 0C. In this paper, partial results from three temperatures are presented. The degradation of insulating liquids was dependent on the type of paper, with the HP having the least negative effect. This work was developed as part of the project number PD-06491-0421/2016, entitled "NOVAS TECNOLOGIAS PARA AUMENTO DA CONFIABILIDADE E VIDA ÚTIL DE TRANSFORMADORES DE POTÊNCIA", an R&D project with participation of VEGOOR, UFSM and Copel Geração e Transmissão SA., within the scope of the Research Program and Technological Development of the Brazilian Electricity Sector regulated by the National Electricity Agency (ANEEL).